2011
DOI: 10.2478/s11534-010-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic tumor growth system with two different kinds of time delay

Abstract: Abstract:The dynamical properties of a noise-driven tumor cell growth system are investigated when there exist two different kinds of time delays, in the deterministic and fluctuating forces, respectively. Using the approximation probability density approach, the delayed Fokker-Planck equation is obtained. The effects of two different time delays on the stationary probability distribution (SPD), the mean value and the mean passage time (MFPT) are discussed. It is found that the time delay τ 1 in the determinis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Many studies have shown that noise and time delay affect the transition between different steady states of tumor populations [19][20][21][22][23][24][25][26][27][28][29][40][41][42][43][44][45][46][47][48][49]. What sets this paper apart from previous research is that Gaussian white noise, Lévy noise and time delay are considered synergistically, and the results provide certain guidance for better study of the growth law of tumors, improve the treatment method of tumors, and enhance the level of tumor treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies have shown that noise and time delay affect the transition between different steady states of tumor populations [19][20][21][22][23][24][25][26][27][28][29][40][41][42][43][44][45][46][47][48][49]. What sets this paper apart from previous research is that Gaussian white noise, Lévy noise and time delay are considered synergistically, and the results provide certain guidance for better study of the growth law of tumors, improve the treatment method of tumors, and enhance the level of tumor treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Stochastic factor disturbance is also inevitable in the tumor growth model, and various noises are usually introduced for simulation. Researchers have looked into how various noises affect tumor growth in the past and have produced a number of significant findings [19][20][21][22][23][24][25][26][27][28][29]. Numerical simulations of the stationary probability density (SPD) of the delayed tumor-immune system in the presence of cross-correlated sine-Wiener noises were investigated by Guo et al [27].…”
Section: Introductionmentioning
confidence: 99%